-6-4n=-26

Simple and best practice solution for -6-4n=-26 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -6-4n=-26 equation:


n in (-oo:+oo)

-(4*n)-6 = -26 // + 26

26-(4*n)-6 = 0

26-4*n-6 = 0

20-4*n = 0 // - 20

-4*n = -20 // : -4

n = -20/(-4)

n = 5

n = 5

See similar equations:

| 4t-5=19 | | -3n+6=-9 | | -2m+9=29 | | 8+6k=-40 | | 4+5k=24 | | -4w+8=-16 | | 4-7a=-10 | | 4d+9=33 | | -7a-8=-8 | | 4b+10=34 | | 3k+10=46 | | -5k+6=-49 | | 3t+2=35 | | 5m+9=19 | | 4d+3=7 | | -5t+2=-8 | | -7t-7=-42 | | 2b-7=5 | | -7k-9=-9 | | 3+5b=-12 | | 4d+5=-35 | | 6n+10=-2 | | -7-6m=23 | | -7d-2=5 | | -6t+8=-46 | | 3(x^2-2)=6 | | 3t+6=36 | | -2k-7=-9 | | 8+4m=-28 | | -9+7k=40 | | 4+4b=-8 | | 3-6d=69 |

Equations solver categories